Family Cooperation in Contracts: Patterns and Trends (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2017)
Cooperation among multiple family members in contracts is a universal phenomenon. At the same time, while in the case of most types of contracts all family members take the same position, in one case, that of the sale of landed property, we note the distinction between one family member, who sells the object, and others, who express their consent. The consent clause is attested not only in Greek papyri from Egypt, but also epigraphical- ly, primarily in manumission inscriptions from Hellenistic Greece, as well as in Demotic acts of sale. A comparative, cross-cultural analysis thus becomes possible.